Pengaruh Lingkungan Kerja, Kompetensi dan Pemberdayaan Terhadap Kinerja Pegawai (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research was conducted because the author observed the conditions at the Ciamis Regency Regional Financial and Asset Management Revenue Office, which showed that some employees had suboptimal performance even though they already had adequate competence. This low performance is caused by a lack of attention and support from leaders, lack of cooperation between divisions, employee competencies that are still below organizational expectations, and rapid development of information technology that is not balanced by the improvement of knowledge, skills, and work attitudes of employees. As a result, the results of the work produced have not been optimal. Many employees lack discipline in carrying out the rules and work procedures set by the organization, which can also be seen from the untimely attendance and the presence of employees who are absent from their duties. Employee empowerment is also uneven because employees who have the necessary skills are limited, so more work is done by certain employees only. The delegation of work is also often not accompanied by a complete explanation to the recipient, causing the completion of the work to exceed the set time target and the quality of the work is not optimal. The purpose of this research is to study, know, and analyze the influence of the work environment, competence, and empowerment on employee performance. This study uses an explanatory survey method with a quantitative approach, as well as descriptive and inferential statistical data analysis techniques with correlation analysis and multiple regression analysis tools. The results of the study show that the work environment, competence, and empowerment are empirically in high condition, and have a significant influence on employee performance. A good work environment, very high competence, and optimal empowerment have a positive effect on high employee performance.